2020
DOI: 10.1002/eap.2109
|View full text |Cite
|
Sign up to set email alerts
|

Landscape structure and climate drive population dynamics of an insect vector within intensely managed agroecosystems

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…No niche shift was found between native and invasive populations of TPP and its associated pathogen CLso. The occupied niches of CLso were found within those of its host TPP and this niche similarity provided us a chance to predict the potential distribution of TPP and as a complex, as it is usually difficult to detect the pathogen [8,21]. Niche comparison further indicated that the climate space occupied by the invasive populations is only a portion of that occupied in their native regions, implying that TPP and CLso may continue to expand their range in Australasia unless efficient biosecurity measures are taken.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…No niche shift was found between native and invasive populations of TPP and its associated pathogen CLso. The occupied niches of CLso were found within those of its host TPP and this niche similarity provided us a chance to predict the potential distribution of TPP and as a complex, as it is usually difficult to detect the pathogen [8,21]. Niche comparison further indicated that the climate space occupied by the invasive populations is only a portion of that occupied in their native regions, implying that TPP and CLso may continue to expand their range in Australasia unless efficient biosecurity measures are taken.…”
Section: Discussionmentioning
confidence: 93%
“…Frequently, predicting an invasion is dependent on prediction of climate suitability using extrapolations made from limited information to project how a species might arrive, establish, or spread in novel environments and impact these environments [19,20]. In particular, a recent study found that the occurrence and abundance of TPP in its native habitat in the USA could be best described by incorporating climate and landscape factors [21]. Here, we applied MaxEnt models with known occurrence data and spatial bioclimatic layers to predict areas climatically suitable for establishment of the TPP/CLso complex on a global scale and then combined information about climate suitability from these models with spatial land use layers to assess the risks of invasion in global potato cultivation areas and major crop production regions in Australia that have recently been invaded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we focused only on Diptera as it is the primary taxa within the diet of Tree swallows nesting in our study system (Bellavance et al 2018). An increase in Diptera availability within more agro-intense landscapes may be expected, at least in some years, due to the susceptibility of arable crops to pest outbreaks (Étilé 2014, Gutiérrez Illán et al 2020). For example, Delia, a genus of Diptera, encompasses several pest species (Savage et al 2016).…”
Section: Discussionmentioning
confidence: 99%